2016
DOI: 10.3389/fnins.2016.00424
|View full text |Cite
|
Sign up to set email alerts
|

Does Prenatal Valproate Interact with a Genetic Reduction in the Serotonin Transporter? A Rat Study on Anxiety and Cognition

Abstract: There is ample evidence that prenatal exposure to valproate (or valproic acid, VPA) enhances the risk of developing Autism Spectrum Disorders (ASD). In line with this, a single injection of VPA induces a multitude of ASD-like symptoms in animals, such as rats and mice. However, there is equally strong evidence that genetic factors contribute significantly to the risk of ASD and indeed, like most other psychiatric disorders, ASD is now generally thought to results from an interaction between genetic and environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 76 publications
3
16
0
Order By: Relevance
“…Furthermore, combination of stress exposure and postnatal SSRI treatment in dams alters affective susceptibility of the offspring in a SERT-dependent manner 206 . Conversely, behavioral alterations produced by in utero VPA exposure were not affected by the presence of SERT 155 . On the other hand, rats with reduced SERT expression, and a previous history of maternal separation, showed improvements in stress-coping responses 207 .…”
Section: Translational Aspects and Concluding Remarksmentioning
confidence: 80%
See 2 more Smart Citations
“…Furthermore, combination of stress exposure and postnatal SSRI treatment in dams alters affective susceptibility of the offspring in a SERT-dependent manner 206 . Conversely, behavioral alterations produced by in utero VPA exposure were not affected by the presence of SERT 155 . On the other hand, rats with reduced SERT expression, and a previous history of maternal separation, showed improvements in stress-coping responses 207 .…”
Section: Translational Aspects and Concluding Remarksmentioning
confidence: 80%
“…However, several studies failed to replicate some of these effects 136 , 137 , 151 . On the other hand, and related to the social deficits observed, a decreased olfactory motivation and sensorimotor capacity were found in VPA-exposed mice 134 , 139 , 142 , 145 , 155 (Table 3 ). Additionally, sex-specific aggressive and defensive strategies in social settings appeared to be affected by the VPA exposure, switching from a defensive tactic to a more aggressive one 161 .…”
Section: Pharmacological Models: Behavioral Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…5-HT signaling facilitates several neural processes including neurogenesis, cell migration and survival, synaptogenesis, and synaptic plasticity. Interestingly, high 5-HT levels in the blood have been described for up to 45% of tested ASD subjects(Chen et al, 2015 , 2017 ; Ellenbroek et al, 2016 ). Moreover, preclinical investigations using ASD-like animal models reported that hyperserotonemia significantly reduced the motivation for social interest through inhibition of separation distress, potentially accounting for the social impairments found in ASD individuals (Ellenbroek et al, 2016 ; Nakai et al, 2017 ).…”
Section: Correlation Of Neurotransmitters Dysfunction To Asdmentioning
confidence: 99%
“…Similarly, several environmental models have been developed based on prenatal immune activation or treatment with valproate [28]. Nevertheless, the animals models that combine genetic and environmental risk factors are rare [29].…”
Section: The Limits Of the Current Generation Of Animal Modelsmentioning
confidence: 99%